2017
DOI: 10.1038/s41467-017-02012-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into TRIP13-catalyzed Mad2 structural transition and spindle checkpoint silencing

Abstract: The spindle checkpoint maintains genomic stability and prevents aneuploidy. Unattached kinetochores convert the latent open conformer of the checkpoint protein Mad2 (O-Mad2) to the active closed conformer (C-Mad2), bound to Cdc20. C-Mad2–Cdc20 is incorporated into the mitotic checkpoint complex (MCC), which inhibits the anaphase-promoting complex/cyclosome (APC/C). The C-Mad2-binding protein p31comet and the ATPase TRIP13 promote MCC disassembly and checkpoint silencing. Here, using nuclear magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 78 publications
1
31
0
Order By: Relevance
“…Since both Mad2 and REV7 form a conformational dimer to recruit downstream effectors, this may be a universal mechanism utilized by HORMA proteins 26 . It is known that Mad2 is regulated by p31 comet and ATPase TRIP13 through structural remodeling 29,30 . However, how shieldin is regulated is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since both Mad2 and REV7 form a conformational dimer to recruit downstream effectors, this may be a universal mechanism utilized by HORMA proteins 26 . It is known that Mad2 is regulated by p31 comet and ATPase TRIP13 through structural remodeling 29,30 . However, how shieldin is regulated is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Recently, Brulotte et al 66 showed that in vitro low levels of TRIP13 were unable to quickly reactivate APC/C Cdc20 that had been pre-incubated with MCC components, but were sufficient to disassemble-free MCC and prevent APC/C Cdc20 inhibition. These data clearly show that free MCC is the preferred substrate of TRIP13, but does not eliminate the possibility of low-level activity on APC/C-MCC complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell pellets were washed 1x with PBS and flash frozen in liquid nitrogen. Ubiquitylation reactions were performed as previously described ( Brulotte et al, 2017 ; Ji et al, 2017 ). Briefly, APC/C was isolated from HeLa cell extracts with anti-APC3 antibody coupled Protein A beads (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%